Antimicrobial and Phytochemical Screening of Plumbago zeylanica Linn. (Plumbaginaceae) Leaf - Markandeya2, D.A. Dhale1* and S.K. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The antimicrobial effect of Plumbago zeylanica Linn. (Plumbaginaceae) leaf extract was evaluated on microbial strains like gram positive species Staphylococcus aureus, and Bacillus subtilis and gram negative species Escherichia coli and Pseudomonas aeruginosa. The solvent used for extraction of plant were petroleum ether, chloroform and alcohol. The alcoholic extract of leaves of Plumbago zeylanica shows maximum antimicrobial activity. The in vitro antimicrobial evaluation was carried out by agar disc diffusion method. The significant antibacterial activity of active extract was compared with standard antibiotic Amphicillin. Ã‚Â The samples of leaves were further used for the phytochemical studies. Results of the phytochemical analysis indicated the presence of alkaloids, glycoside, reducing sugars, simple phenolics, tannins, Lignin, saponins and flavonoids. The antibacterial activities of the leaves were due to the presence of various secondary metabolites.